Literature Review Tax Minization, Tunneling Incentive, Debt Covenant, Bonus Mechanisms and Good Corporate Governance on Transfer Pricing - Rio Baviga; Afrizal Afrizal; Wirmie Eka Putra; Rico Wijaya Z (Citakonsultindo, 2024)
This research provides criticism of literature that examines and analyzes how Tax Minization, Tunneling Incentive, Deb Covenant, Bonus Mechanisms and Good Corporate Governance affect Transfer Pricing. The problem discussed in this research is to see the extent of the influence of Tax Minization, Tunneling Incentive, Deb Covenant, Bonus Mechanisms and Good Corporate Governance on Transfer Pricing. Based on the literature studied, there is an influence between Tax Minization, Tunneling Incentive, Deb Covenant, Bonus Mechanisms and Good Corporate Governance on Transfer Pricing.